Correlation of Point of Care Ultrasound (POCUS) Guided Pupillary Assessment Parameter with Glasgow Coma Scale in Patients with Altered Mental Status- A Cross Sectional Study - Priyanka Modi; Sanjeev Bhoi (CINQUILL Medical Publishers Inc., 2024)
Background: Earlier studies have proved deteriorating Glasgow Coma Scale (GCS) as a marker of raised intracranial pressure (ICP). Low GCS is associated with abnormal pupillary parameters. Currently, many studies have proved that ultrasound provides a feasible and objective assessment of pupillary light reflex. However, literature is lacking to evaluate objective pupillary parameters to predict GCS of the patients by point of care ultrasound (POCUS). Materials and methods: In this prospective, cross-sectional study, 200 patients were recruited in the emergency department. The inclusion criteria were patients older than 18 years with acute presentation of altered mental status. Exclusion criteria were patients who had partial globe rupture or dementia. The patients underwent a B-mode POCUS-guided evaluation at rest and after light stimulation. Statistical analysis of relationship between pupillary assessment parameters and GCS was performed using Spearman's Rank correlation coefficient, Kruskal-Wallis equality-of-populations rank test, and area under the receiver operating characteristic. Results: The study consisted of 200 (42 female, 158 male) patients with mean (± standard deviation) of age and GCS of 43.56 ± 16.50 years and 5.54 ± 3.00, respectively. Majority of non-reactive pupils had a GCS Score of 3-8 (74 cases, 97.37%). The Pupillary diameter (PD) and PD variation showed statistically significant agreement with pupil reactivity to light stimulation and GCS, with Spearman's correlation coefficient ranging from 0.28 to 0.33 for PD, and -0.55 to -0.50 (p-value <0.05) for PD variation, respectively. PD variation rate (PDVR) is the percentage change in the magnitude of constriction of PD on light stimulation. PDVR of >19.68% had a sensitivity of 86.96% (95% CI: 82.04 - 91.88%) and specificity of 64.97% (95% CI: 58.00 - 71.94%) to detect GCS>8. Conclusion: PD variation and PDVR measured by POCUS has significant correlation with GCS >8. The study showed good sensitivity and low specificity of PDVR on light stimulation to detect GCS >8.